2016
DOI: 10.4137/cmamd.s38090
|View full text |Cite
|
Sign up to set email alerts
|

Apolipoprotein E Gene Polymorphisms in Saudi Patients with Systemic Lupus Erythematosus

Abstract: Apolipoprotein E (APOE) is a glycosylated protein with multiple biological properties. APOE gene polymorphism plays a central role in lipid metabolism and has recently been suggested to regulate inflammation. Our objective is to evaluate whether APOE polymorphism affects susceptibility to SLE. APOE genotyping was performed using ApoE StripAssay™ kit. Results indicated significantly higher frequencies of allele ε4 and genotype ε3/ε4 and lower frequencies of allele ε3 and genotype ε3/ε3 in SLE patients than cont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 65 publications
0
7
0
Order By: Relevance
“…35 Another study concluded that APOE allele ε4 is associated with susceptibility risk/clinical manifestations of SLE. 38 Finally, a previous study suggested that APOE ε4 presence leaves patients with IDDM more susceptible to cognitive decline at a younger age, possibly through vascular pathways. 39 Previous studies have also found that APOE ε4 has associations with TLE (e.g., nonlesional mesial temporal lobe epilepsy) via various mechanisms (e.g., amyloid deposition in the brain and impairment of nerve damage repair mechanisms).…”
Section: Apoe ε4mentioning
confidence: 97%
See 2 more Smart Citations
“…35 Another study concluded that APOE allele ε4 is associated with susceptibility risk/clinical manifestations of SLE. 38 Finally, a previous study suggested that APOE ε4 presence leaves patients with IDDM more susceptible to cognitive decline at a younger age, possibly through vascular pathways. 39 Previous studies have also found that APOE ε4 has associations with TLE (e.g., nonlesional mesial temporal lobe epilepsy) via various mechanisms (e.g., amyloid deposition in the brain and impairment of nerve damage repair mechanisms).…”
Section: Apoe ε4mentioning
confidence: 97%
“…The first SNP was rs16944 on the Interleukin-1β (IL-1β) gene; different studies reported the associations between this gene variation and TLE, 27 RA, 28,29 SLE, 30 and IDDM. 31 The second genetic variation was ε4 variation of apolipoprotein E (APOE) gene that was associated with TLE, [32][33][34] RA, 35,36 SLE, 37,38 and IDDM. 39,40 None of the above references and studies had patients with serologically proven autoimmune epilepsy.…”
Section: Bullet Pointsmentioning
confidence: 99%
See 1 more Smart Citation
“…Genetic studies of SLE among Arab patients in the GCC region are generally scarce in the literature, and extremely rare regarding LN. Some of SLE susceptibility genes have been recently reported and/or investigated in SLE patients in the GCC region, such as HLA alleles, 29,30 C1Q, 31,32 ISG15, 33 APOE, 34 PTEN, 35 and PNP 36 genes in Saudi patients; and IRF5, 37 PTPN22, 38 ACE, 39 eNOS, 40,41 and CTLA4 42,43 genes in Kuwaiti patients. Of note, Al-Mayouf et al 44 identified a rare autosomal recessive monogenic form of SLE in Arab patients in Saudi Arabia, caused by a null mutation in the DNASE1L3 gene, and correlated with a high frequency of LN.…”
Section: Genetic Studies Of Sle/ln In the Gcc Regionmentioning
confidence: 99%
“…It has also been reported that 36% of patients with newly diagnosed SLE have hypercholesterolemia (3), suggesting a relationship between the dysregulation of lipid metabolism and autoimmune responses. Consistently, recent genome-wide association studies and expression quantitative trait loci analyses have revealed that genes involved in lipid metabolism increase the susceptibility to autoimmune diseases such as rheumatoid arthritis and SLE (4)(5)(6). However, the molecular mechanism by which lipid metabolism influences the pathology of SLE is unclear.…”
Section: Introductionmentioning
confidence: 98%